2021
DOI: 10.1021/acsestengg.1c00366
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis of >20 g/L H2O2 from Air

Abstract: Hydrogen peroxide (HP) production via electrochemical oxygen reduction reaction (ORR-HP) is a critical reaction for energy storage and environmental remediation. The onsite production of high-concentration H 2 O 2 using gas diffusion electrodes (GDEs) fed by air is especially attractive. However, many studies indicate that the air–GDE combination could not produce concentrated H 2 O 2 , as the [H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Electrolysis during our iron electrocoagulation experiments generated 0.18 mM Fe­(II) along with 19 μM H 2 O 2 attributed to the cathodic reduction of dissolved oxygen (accompanied by dissolved oxygen depleting from 265 to 225 μM). The simultaneous presence of Fe­(II) and H 2 O 2 (and dissolved oxygen) strongly implies the initiation of electro-Fenton reactions that generate reactive oxygen species like • OH and oxoiron (IV), , which are capable of inactivating viruses. , This phenomenon can also be exploited to mitigate bacteria and oxidize recalcitrant contaminants , via iron electrocoagulation, notwithstanding electrode passivation …”
Section: Resultsmentioning
confidence: 99%
“…Electrolysis during our iron electrocoagulation experiments generated 0.18 mM Fe­(II) along with 19 μM H 2 O 2 attributed to the cathodic reduction of dissolved oxygen (accompanied by dissolved oxygen depleting from 265 to 225 μM). The simultaneous presence of Fe­(II) and H 2 O 2 (and dissolved oxygen) strongly implies the initiation of electro-Fenton reactions that generate reactive oxygen species like • OH and oxoiron (IV), , which are capable of inactivating viruses. , This phenomenon can also be exploited to mitigate bacteria and oxidize recalcitrant contaminants , via iron electrocoagulation, notwithstanding electrode passivation …”
Section: Resultsmentioning
confidence: 99%
“…By using a superhydrophobic natural air diffusion electrode (NADE) to improve the oxygen diffusion coefficient at the cathode as compared to the normal gas diffusion electrode (GDE) system, Zhang et al showed that it is possible to largely increase the H 2 O 2 production rate and oxygen utilization efficiency. These examples show how a deep understanding of the engineering aspects at the electrode nanoscale is a crucial factor in determining the behavior, and not only the nature, of the electrode itself . Quite similar aspects also strongly determine the behavior in NRR .…”
Section: Limits and Gaps In Catalysis For E-chemistrymentioning
confidence: 88%
“…These examples show how the deep understanding of the engineering aspects at the electrode nanoscale is the crucial factor in determining the behaviour, and not only the nature, of the electrode itself. 115 Quite similar aspects are also strongly determining the behaviour in NRR. 116 Produce H2O2 rather than O2 in water splitting or other electrocatalytic reduction reactions (CO2RR and NRR) has thus the advantages of making a 2erather than a 4eprocess (with advantages in terms of rate and reduced overpotential), and obtain a higher value product.…”
Section: Figure 2 Herementioning
confidence: 97%
“…Additionally, electrode preparation methods should be carefully described, as the catalyst microstructure can affect the diffusion of O 2 and H 2 O 2 into and out of the electrode, , which can further impact the ability for H 2 O 2 to accumulate and the Faradaic efficiency. Some factors to consider include the catalyst ink compositions (solvents, ionomers, catalyst concentrations), , the properties of the electrode substrates (hydrophobicity, porosity), , and the methods of depositing the catalyst onto the electrodes (drop-casting, spray-coating, or direct growth ). Because many factors at the device, electrode, and catalyst levels can impact the overall electrosynthesis performance, comparing the apparent H 2 O 2 electrosynthesis performances under different cell conditions can further obfuscate atomic-level insights into the structural design of metal-compound-based 2e – ORR catalysts.…”
Section: Device Engineering For Practical Electrosynthesis Of H2o2mentioning
confidence: 99%